(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
This study aspired to investigate the effect of different doses of exogenous GA3 (viz. o, 10, 30, 50, 70, 90 and 110 ppm) on leaf pigments like chlorophyll a, chlorophyll b and carotenoid, yield and proximate contents of fresh pod and dry seed of Bush bean(Phaseolus vulgaris L.). Different concentrations of GA3 significantly increased chlorophyll a, chlorophyll b and carotenoid at 28 to 48 DAS growth stages. Early flowering and maturation were recorded by GA3. It was found that number of pods/plant, pod weight, pod length and pod width also significantly increased by GA3. All the treatments showed a significant increase of crude protein, crude fiber and ash content, whereas total carbohydrate and crude fat decreased in respect of fresh pod and dry seed of Bush bean. It had no significant effect on pod moisture compared to the control. Among all the treatments, GA3 at 50 ppm gave the best performances in tested parameters. Asiat. Soc. Bangladesh, Sci. 41(2): 245-251, December 2015